Estrogen-related receptors: novel potential regulators of osteoarthritis pathogenesis - Jinshuo Tang; Tong Liu; Xinggui Wen; Zhongsheng Zhou; Jingtong Yan; Jianpeng Gao; Jianlin Zuo (BMC, 2021)
Abstract Osteoarthritis (OA) is a chronic inflammatory disease that is associated with articular cartilage destruction, subchondral bone alterations, synovitis, and even joint deformity and the loss of joint function. Although current basic research on the pathogenesis of OA has made remarkable progress, our understanding of this disease still needs to be further improved. Recent studies have shown that the estrogen-related receptor (ERR) family members ERRα and ERRγ may play significant roles in the pathogenesis of OA. In this review, we refer to the latest research on ERRs and the pathogenesis of OA, elucidate the structure and physiopathological functions of the ERR orphan nuclear receptor family, and systematically examine the relationship between ERRs and OA at the molecular level. Moreover, we also discuss and predict the capacity of ERRs as potential targets in the clinical treatment of OA.